Is non-operative management of acetabular fracture a viable option for older patients? A systematic review of the literature for indication, treatments, complications and outcome - Cacciola, Giorgio; Aprato, Alessandro; Branca Vergano, Luigi; Sallam, Adel; Massé, Alessandro (Acta Biomedica Atenei Parmensis, 2022)
There is no consensus about the best treatment for acetabular fracture in older patients. The purpose of this study was to review the current literature looking for indication, perioperative information and outcome of nonoperative management for acetabular fractures in elderly.A systematic review of literature was performed on different research database by using various combination of the keywords “acetabular fracture”, “elderly patients”, “60 years”, “nonoperative”, “nonsurgical” and “conservative treatment”.Six articles met our inclusion criteria, 315 patients aged 60 or more treated nonoperatively for acetabular fracture were included in the analysis. The average age was 78.1 years, the average follow-up length was 48.7 months. The main criteria for indication of nonoperative management for acetabular fractures were, old age (75 years or more), two or more important medical comorbidities, and minimally or undisplaced fracture. The most frequent fracture pattern was anterior column in 25.3% of cases. Fall from standard height was the most frequent causative mechanism in 80% of patients. A conversion total hip arthroplasty was performed after 8.3% of cases. A 1-year mortality of 18% was reported, an overall mortality of 33.1% at last follow-up was reported.The management of acetabular fractur in elderly is a challenging problem and there is no consensus about the best treatment. Currently, multiple treatment options have been suggested, depending on fracture pattern and patients’ general conditions. Although operatively treatment allow for an early recovery, there is not an high level of evidence about the superiority in terms or complications and mortality rate compared to nonoperative treatment.